Arachnofauna (Arachnida) of Isla del Coco, Costa Rica, with description of three new species. - Víquez, Carlos (2020)
Introduction: The arachnids of Isla del Coco represent 50 species, located in six orders and 26 families. The work of updating the knowledge of the fauna of this group of animals on the island began not systematically more than 127 years ago, where a scorpion became the first specimen cited in the group. Objective: To update the list of arachnid species for Coco Island, providing new information about little-known taxa and describing new species. Methods: During two expeditions, carried out from April 11 to 22, 2013 and from July 8 to 18, 2017, arachnids were collected with manual methods and traps, preserved in ethanol and identified in the laboratory. The distribution ranges are based on the spiders catalog of the world, the identifications made, are supported by the specific literature cited for each case and the biogeographical suggestions presented of the groups or species treated, arise from the analysis of the general distribution patterns that presents the genus or group cited. Results: The main findings include the addition of new species records for the island, one order, 11 families and 29 species, of which three are new to science. Conclusions: It is necessary to continue with the inventory of the island fauna, mainly in the sectors that could not be previously sampled. At the biogeographical level, the spider fauna that inhabits the island is mostly related to Central America, while the species with cosmopolitan habits are possibly of recent introduction.